Probiotics for Everyone! The Novel Immunobiotic Lactobacillus rhamnosus CRL1505 and the Beginning of Social Probiotic Programs in Argentina - Villena, Julio Cesar (2012)
Lactobacillus rhamnosus CRL1505 (Lr1505) stimulates immune responses in the gut and in the respiratory tract and improves resistance against Salmonella typhimurium and Streptococcus pneumoniae infections in immunocompetent and immunocompromised mice. Considering that respiratory infectious diseases continue to be a major cause of death among preschool children in developing countries, the aim of the present study was to evaluate the effect of Lr1505 on the health of children. A randomized-controlled double-blind clinical trial in 298 healthy children (2-5 years old), attending daycare centers was performed. Yogurt containing Lr1505 was administered to children for 6 months (five times a week). Results were statistically compared with those of children from the same community that received a placebo yogurt (without probiotic). Administration of Lr1505 to young children reduced the incidence of infections: 66% of children in the placebo group presented symptoms of infection while only 34% of cases were detected in the Lr1505 group. Significant differences (P<0.05) were detected in the incidence of intestinal infections, upper respiratory tract infections and angina when placebo and Lr1505 groups were compared. Children fed Lr1505 experienced fewer fevers and needed fewer antibiotics than those receiving the placebo. The protective effect of Lr1505 was associated with increased levels of mucosal IgA antibodies. Lr1505 is a promising resource for the development of prevention strategies against mucosal infections that could be effective tools for medical application. This new probiotic strain has been included into official Nutritional Programs in Argentina and it is given to more than 200 thousand children. This project has encouraged local milk production, thanks to the constant demand of probiotic yogurt containing L. rhamnosus CRL1505 by provincial governments, while incorporating innovation to small and medium enterprises.